Why sanctions on Russia did not work well? Russia's economic resistance against the sanctions in 2022 - Zhang, Xuan (Nanyang Technological University, 2023)
With the Russian force invading Ukraine, US-led Western countries launched a blanket of economic sanctions to punish Russia and restrained its’ military capability on the battlefield. However, Russia’s economy outperformed many financial institutions and economists’ forecasts and raise many debates on the economic effectiveness of sanctions on Russia. This essay will explore the reason why Russia’s economy is resistant and resilient under economic sanctions. Through the review of previous academic studies on sanctions and the comparison with sanctions starting from 2014, this paper finds out some pre-conditions of the Russian economy make it suffer less impact from the sanctions such as its overall economic size and economic structure. Despite these preconditions that existed before the imposition of the sanctions, some new dynamics like high oil prices, strong exchange rates, and increasing ties with non-sanction states, also emerged in 2022’s sanctions on Russia and play a significant role in the mitigation of sanctions.